The endangered Arctic fox in Norway—the failure and success of captive breeding and reintroduction. (8th September 2017) - Landa, Arild; Flagstad, Øystein; Areskoug, Veronika; Linnell, John D. C.; Strand, Olav; Ulvund, Kristine Roaldsnes; Thierry, Anne-Mathilde; Rød-Eriksen, Lars; Eide, Nina E.
ABSTRACT: The Arctic fox ( Vulpes lagopus L.) is listed as extinct in Finland, endangered in Sweden and critically endangered in Norway. Around 2000 there were only 40–60 adult individuals left, prompting the implementation of conservation actions, including a captive breeding programme founded from wild-caught pups. The initial breeding trials failed, probably because of stress among captive animals, and the programme was radically changed in 2005. Eight large enclosures within the species' historical natural habitat were established, which had the positive effect of all pairs breeding in 2007. As of 2015, 385 pups (yearly average 37) were produced. In this ongoing programme, pups are released the winter (January–February) following their birth and have had an average first-year survival of 0.44. The release sites are prepared with artificial dens and a network of supplementary food dispensers, designed to work exclusively for the Arctic fox. After just four to seven years of releases, populations have been effectively re-established in three mountain areas where the species had been locally extinct. One of the newly re-established populations has become the largest population in Norway. Several other populations, including Swedish ones, have benefited considerably from successful immigration of released foxes. The number of wild-born pups that are descendants of released foxes has likely exceeded 600, and in 2014 50% of all free-living breeding pairs in mainland Norway included released foxes or their descendants. The Norwegian Arctic fox captive breeding programme has proven to be an important conservation action for the recovery of the Scandinavian Arctic fox population.